MATHEMATICAL MODELS FOR ESTIMATING LEAF AREA OF APRICOT AND JUJUBE PLANTS BASED ON LEAF LENGTH AND WIDTH - M. E. A. Al-Hadethi; F. S. H. Al-Marsoumi (مجلة الأنبار للعلوم الزراعية)
This research involved 14 apricot and 9 jujube cultivars from which 50 leaves each were taken for a total of 700 apricot and 450 jujube leaves. Leaf length and width were measured and leaf area (LA) calculated based on three methods: a square method drawing on graph paper; using a CI-202 area-meter device; and scanning and reading using a Digimizer program. The average leaf area from the three methods was calculated and linear regression analysis was used based on leaf length × width as independent variables. A mathematical model was then developed to calculate the leaf areas for both cultivar types. The coefficient of determination (R2) values of the leaves were 0.155 and 0.998 for the local Zaghinia and Hamwi cultivars, while the MSE values ​​were 0.071 and 34.273 for the Hamwi and Katy cultivars, respectively. For the LA models, the Hamwi cultivar model (LA= 0.6568 (LW) + 0.8683) was dominant. The general mathematical model estimated from this regression for the cultivars is LA= 0.6531 (LW) + 2.4147 with an R2 of 0.976. As for the jujube plants, results showed that R2 values were between 0.618 and 0.954 for the Basrah and Baghdad seed cultivars, while the MSE values were between 0.615 and 8.610 for the Mallasi and Tuffahy cultivars, respectively. Among the LR models, the Armouty cultivar (LA= 0.6648 (LW) +1.7625) stood out. The general mathematical model estimated from this regression using the jujube cultivars is LA= 0.7528 (LW) + 0.0241 with R2 of 0.987.